Albania : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Despite a stern global financial crisis and fiscal imbalances within the country, Albania's prudent policies supported its economy to grow and safeguarded the soundness of the financial system. The Executive Board of the International Monetary Fund (IMF) encouraged the authorities to use prospective privatization receipts mainly for debt reduction and clearance of unpaid bills. The Directors recognized that financial risks remained elevated, and called for continued supervisory vigilance. They stressed the need to accelerate structural reforms in many areas to boost potential growth.